Analisis Preferensi Konsumen Wortel Organik (Daucus carota L.) di Kota Semarang (Studi Kasus: Komunitas Pasar Sehati Semarang) - Prisanti, Andara Nuradika; Prastiwi, Wahyu Dyah; Handayani, Migie (Universitas Galuh, 2024)
The research aimed to analyze the combination of organic carrot attributes preferred by consumers and to analyze the consumer preference attributes most considered when purchasing organic carrots at Pasar Sehati Semarang. The research was conducted from January to March 2024 at Pasar Sehati Semarang, Semarang City. The location was purposively selected considering that Pasar Sehati Semarang is managed by the Pasar Sehati Semarang Community, which sells healthy food products. The research method used was a case study method. The research respondents were organic carrot consumers at Pasar Sehati Semarang, Semarang City. Respondent selection was conducted using accidental sampling and purposive sampling methods with a total of 100 respondents sampled online and offline. The data used in this research were primary and secondary data. The obtained data were analyzed using quantitative descriptive analysis and Conjoint analysis. Quantitative descriptive analysis was used to explain the processed data in the research results. Conjoint analysis was used to analyze consumer preferences for the levels of organic carrot attributes, which consist of price, size, color, and packaging. The Conjoint analysis results revealed that the consumer preference for organic carrots at Pasar Sehati Semarang was for carrots with a price of <Rp30,000/kg; large size, bright orange color, and packaged in styrofoam trays. The attribute considered most important by consumers when purchasing organic carrots is the price. Marketers should consider the selling price range more to suit consumer desires and develop packaging strategies that consumers prefer, namely Styrofoam tray.